Development of Tannin Modified Membrane for Spectrophotometric Determination of Lead - Ratanawimarnwong, Nuanlaor; Suksomphot, Vanlada; Mantim, Thitirat; Karuwan, Chanpen (Science Essence Journal, 2023)
Tannin modified membrane (TM) was developed for preconcentration and detection of trace level of lead (Pb) using a complex formation between Pb2+ and (4-2-pyridylazo)-resorcinol (PAR). The extraction membrane was prepared by immobilizing tannin on a rectangular cellulose filter paper sized 7 x 9 cm2 and then cut into a small circular shape of 13-mm diameter to fit with a commercially available syringe filter holder. The 4-layered of the TMs was employed for preconcentration of Pb2+. An aliquot of 50 mL of standard or sample containing Pb2+ was loaded by using a 50-mL syringe that connected with a filter holder. To accelerate speed of analysis, peristaltic pump was used by connecting to a bottom side of the filter holder. For loading step, a flow rate of 4.4 mL/min was used. Elution of Pb2+ was accomplished by manually passing 5 mL of 0.1 M HCl through the membrane. An aliquot of 3 mL of the eluent was then mixed with the PAR reagent under the controlled pH of 9. Absorbance of 522 nm was monitored. Various optimization parameters affecting the immobilization of tannin on the cellulose filter paper were investigated. Under optimized conditions, linear calibration was obtained from 0.1 mg/L to 1.25 mg/L of Pb2+ solution. Acceptable precision of 2.0% (n = 5) was obtained. Good recoveries of 90.40 and 91.99 were achieved for drinking water samples.